1998
DOI: 10.1128/iai.66.4.1613-1621.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Carbohydrate Moiety of Intestinal Mucin-Type Sialoglycoprotein Receptors for the K88ac Fimbrial Adhesin of Escherichia coli

Abstract: We have previously identified two mucin-type sialoglycoproteins from porcine intestinal epithelial cells with approximate molecular masses of 210 (intestinal mucin-type glycoprotein IMTGP-1) and 240 kDa (IMTGP-2) as receptors for the K88ab and K88ac fimbrial adhesins ofEscherichia coli. These receptors are detected in intestinal brush border membrane preparations from pigs with adhesive phenotypes but not from pigs with nonadhesive phenotypes and are postulated to be important determinants of the susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 36 publications
(43 reference statements)
3
20
1
Order By: Relevance
“…In present study, K88ac and K88+MB speci¢c receptors in small intestinal mucus were found to be, at least in part, glycoprotein in nature, judging by the result that treatment of intestinal mucus with either proteolytic enzyme or sodium metaperiodate greatly reduced the degree of adhesion of E. coli K88ac or K88+MB. These results agree with Erickson et al [13] and Grange et al [16] who reported that E. coli K88ac adhesion receptors in porcine intestinal brush border cells are mucin-type sialoglycoproteins. Earlier, Sellwood et al [19] and Anderson et al [22] reported that glycoproteins are involved in the attachment of K88 ¢mbriae to intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In present study, K88ac and K88+MB speci¢c receptors in small intestinal mucus were found to be, at least in part, glycoprotein in nature, judging by the result that treatment of intestinal mucus with either proteolytic enzyme or sodium metaperiodate greatly reduced the degree of adhesion of E. coli K88ac or K88+MB. These results agree with Erickson et al [13] and Grange et al [16] who reported that E. coli K88ac adhesion receptors in porcine intestinal brush border cells are mucin-type sialoglycoproteins. Earlier, Sellwood et al [19] and Anderson et al [22] reported that glycoproteins are involved in the attachment of K88 ¢mbriae to intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Westerman et al [15] reported that the K88ac variant is the most common, if not the only, variant of K88 adhesin found in pathogenic E. coli isolates from the major pork-producing region of the US. Most of the studies have been concerned with the characterization of receptors of K88ab ¢mbriae [6,7,8,12,14] and K88ac ¢mbriae receptors on intestinal brush border cells [13,16,17]. Few detailed studies on the K88ac ¢mbrial receptor in intestinal mucus are available.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during inhibition via exclusion, other functions such as the ability to produce antimicrobial substances is important for enhancing the hostile microenvironment mediated by coaggregation (Collado et al 2008). On the other hand, for inhibition via displacement, receptor affinity of the adhesins is also important aside from overall adhesion, such as the way beta-linked galactose is essential for recognition by the E. coli K88ac adhesin (Grange et al 1998). Cunliffe et al (1999) also showed that S. Typhimurium may use a different mode of cell attachment compared to E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…+), utilized; (À), not utilized. *Glycoside components of pig intestinal type mucins according toGrange et al (1998).…”
mentioning
confidence: 99%
“…Galactosebinding specificity has been reported for a number of pathogens that attach to intestinal epithelium. For example, enterotoxigenic E. coli attach to the intestine of pigs using F4 (K88) fimbriae, which recognize terminal b1-linked galactose in glycosphingolipids (Coddens et al, 2011) and glycoproteins (Grange et al, 1998). Although F4 fimbriae belong to the FGS CU systems, the F4 fibre acts as a polyadhesin by displaying its binding site on the structural subunit FaeG.…”
Section: Discussionmentioning
confidence: 99%